Water-based resin composition, coating film, method for producing coating film, water-based resin composition set
Patent Information
- Application Number
- CN202280038918.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-02
- Filing Date
- 2022-05-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-05-27
AI Technical Summary
[0060] According to the present invention, an aqueous resin composition and an aqueous resin composition kit can be provided, which can be cured by short-time curing at room temperature to form a coating film with excellent initial water resistance and can obtain a coating film with good humid heat adhesion to metal materials.
Smart Images

Figure BDA0004576927460000041 
Figure BDA0004576927460000251 
Figure BDA0004576927460000252
Abstract
Description
Technical Field
[0001] This invention relates to waterborne resin compositions, coatings, methods for manufacturing the same, and kits of waterborne resin compositions.
[0002] This application claims priority based on Japanese Patent Application No. 2021-092839, filed in Japan on June 2, 2021, the contents of which are incorporated herein by reference. Background Technology
[0003] Generally, the surface of metal products needs to be treated. In particular, metal products used outdoors, as well as those expected to be exposed to moisture, are often coated to prevent rust.
[0004] Traditionally, coatings containing organic solvents have been used for surface coating of metal products. However, when applying coatings containing organic solvents to the surface of metal products, measures must be taken to address volatile organic compounds (VOCs) for operators and the surrounding environment. Therefore, there is a growing trend towards using water-based coatings instead of those containing organic solvents for surface coating of metal products.
[0005] Patent Document 1 discloses a thick coating composition comprising an emulsion composition formed by dispersing polymer particles in an aqueous medium and aggregate. The polymer particles disclosed in Patent Document 1 are manufactured by emulsion polymerization of structural units formed by polymerizing alkyl (meth)acrylate monomers having 4 to 14 carbon atoms, structural units formed by polymerizing olefinically unsaturated carboxylic acid monomers, and structural units formed by polymerizing other monomers, in the presence of a compound having at least two epoxy groups per molecule and an alkaline catalyst.
[0006] Patent Document 2 describes a composition comprising an aqueous dispersion of thermoplastic polymer particles that has absorbed a curable compound having an ethylene oxide alkyl group. Furthermore, Patent Document 2 describes that the polymer particles possess an anti-agglomeration functional group concentration sufficient to stabilize the latex relative to agglomeration.
[0007] Patent document 3 describes a method of forming an acrylic resin (acrylic / epoxy latex) that has absorbed epoxy compounds by mixing an epoxy emulsion into an acrylic resin emulsion.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2011-89092
[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-65914
[0012] Patent Document 3: International Publication No. 2017 / 112018 Summary of the Invention
[0013] The problem that the invention aims to solve
[0014] However, in waterborne resin compositions used for coating the surfaces of metal products, the initial water resistance and humid heat adhesion of the cured coating film still need further improvement. In particular, waterborne resin compositions used for anti-corrosion coating of outdoor metal products such as iron towers, bridges, ships, and harbor facilities require improved initial water resistance of the cured coating film for the following reasons.
[0015] In other words, the coating film formed using a paint containing a water-based resin composition exhibits water resistance through the curing reaction of the resin contained in the coating film. Therefore, after a paint containing a water-based resin composition is applied to a metal product to form a coating film, moisture generated by rainfall or other factors may reach the metal surface through the uncured coating film and cause rust before full curing. Therefore, for water-based resin compositions used in the above-mentioned applications, it is required that they can be cured by short-term curing at room temperature to form a coating film exhibiting superior initial water resistance.
[0016] The present invention was made in view of the above circumstances, and its object is to provide a water-based resin composition and a water-based resin composition kit, which can be cured by short-time curing at room temperature to form a coating film with excellent initial water resistance, and can obtain a coating film with good humid heat adhesion to metal materials.
[0017] In addition, an object of the present invention is to provide a coating film composed of a cured product of the aqueous resin composition of the present invention, and a method for manufacturing the coating film.
[0018] Problem-solving methods
[0019] In order to achieve the above objectives, the present invention is configured as described below in [1] to
[18] .
[0020] The present invention provides a composition of the following first embodiment.
[0021] [1] An aqueous resin composition comprising an aqueous resin emulsion (α), a curing agent (β), and a curing accelerator (γ);
[0022] The aqueous resin emulsion (α) comprises a copolymer (X), a polyepoxide compound (Y) having two or more epoxy groups per molecule and no olefinic unsaturated bonds, and an aqueous medium (Z).
[0023] The content of the polyepoxide (Y) is 1 to 40% by mass relative to the total amount of the copolymer (X) and the polyepoxide (Y).
[0024] The copolymer (X) comprises structural units derived from (meth)acrylate (A) and structural units derived from olefinic unsaturated carboxylic acids (B).
[0025] The content of the structural unit derived from (meth)acrylate (A) is 20-98% by mass relative to the total amount of the copolymer (X) and the polyepoxide (Y).
[0026] Relative to the total amount of the copolymer (X) and the polyepoxide compound (Y), the content of the structural unit derived from the olefinic unsaturated carboxylic acid (B) is 0.1 to 10% by mass, and the structural unit derived from (meth)acrylate (A) includes a structural unit derived from hydrophilic (meth)acrylate (A1), wherein the alcohol-derived portion of the hydrophilic (meth)acrylate (A1) has 2 or fewer carbon atoms.
[0027] The content of the structural unit derived from the hydrophilic (meth)acrylate (Al) is 15-98% by mass relative to the total amount of the copolymer (X) and the polyepoxide (Y).
[0028] One or both of the copolymer (X) and the polyepoxide compound (Y) contain a carboxyl group.
[0029] The curing agent (β) comprises an aromatic polyamine (F) having active hydrogen atoms that are reactive to epoxy groups.
[0030] Regarding the content of the aromatic polyamine (F) contained in the curing agent (β), relative to the amount of epoxy groups contained in the aqueous resin emulsion (α), the amount of active hydrogen contained in the aromatic polyamine (F) is 0.10 equivalents or more and 1.50 equivalents or less.
[0031] The curing accelerator (γ) comprises a tertiary amine, which does not have active hydrogen atoms reactive to epoxy groups.
[0032] The content of the curing accelerator (γ) is 0.0070 mol or more and 1.5 mol or less relative to the epoxy group equivalent contained in the aqueous resin emulsion (α).
[0033] The first embodiment of the present invention preferably has the following features. It is also preferred that two or more of the following features be combined.
[0034] [2] According to the aqueous resin composition of [1], the (meth)acrylate (A) is composed of (meth)acrylate alkyl ester.
[0035] [3] According to the aqueous resin composition of [1] or [2], the olefinic unsaturated carboxylic acid (B) comprises at least one of α,β-unsaturated monocarboxylic acid, α,β-unsaturated dicarboxylic acid and a vinyl compound containing a carboxyl group.
[0036] [4] The aqueous resin composition according to any one of [1] to [3], wherein the polyepoxy compound (Y) is selected from at least one of bisphenol type epoxy compounds, hydrogenated bisphenol type epoxy compounds, diglycidyl ether, triglycidyl ether, tetraglycidyl ether, diglycidyl ester, triglycidyl ester and tetraglycidyl ester.
[0037] [5] The aqueous resin composition according to any one of [1] to [4], wherein the copolymer (X) is composed of the structural units derived from (meth)acrylate (A) and the structural units derived from olefinic unsaturated carboxylic acids (B).
[0038] [6] The aqueous resin composition according to any one of [1] to [4], wherein the copolymer (X) comprises structural units derived from an olefinically unsaturated aromatic compound (C) having a benzene ring and olefinically unsaturated bonds.
[0039] [7] According to the aqueous resin composition of [6], the olefinic unsaturated aromatic compound (C) is an aromatic vinyl compound.
[0040] [8] The aqueous resin composition according to any one of [1] to [7], wherein the aromatic polyamine (F) comprises an aromatic polyamine having two or more benzene rings per molecule.
[0041] [9] The aqueous resin composition according to any one of [1] to [8], wherein the aromatic polyamine (F) comprises a compound represented by the following general formula (1-1),
[0042]
[0043] In equation (1-1), A 2 A 3 Each of these can be used independently to represent 1,2-phenylene, 1,3-phenylene, or 1,4-phenylene. n represents an integer from 1 to 12.
[0044]
[10] According to the aqueous resin composition of [9], the aromatic polyamine (F) comprises the compound represented by the above general formula (1-1) and m-phenylenediamine.
[0045]
[11] In any one of the aqueous resin compositions according to [1] to
[10] , the curing accelerator (γ) is at least one compound selected from aliphatic tertiary amines, alicyclic tertiary amines, and heteroaromatic tertiary amines.
[0046]
[12] The aqueous resin composition according to any one of [1] to
[11] , wherein the aqueous resin emulsion (α) is an emulsion formed by emulsion polymerization of monomers forming the structural units of the copolymer (X) in the aqueous medium (Z) in the presence of the polyepoxide compound (Y).
[0047]
[13] In any one of [1] to
[12] , the aqueous resin composition contains 0.10 × 10⁻⁶ carboxyl groups in the total amount of the copolymer (X) and the polyepoxide compound (Y). -4 Above mol / g.
[0048]
[14] In any one of [1] to
[13] , the aqueous resin composition contains 0.50 × 10⁻⁶ epoxy groups in the total amount of the copolymer (X) and the polyepoxide compound (Y). -4 Above mol / g.
[0049] The second aspect of the present invention provides the coating as described below.
[0050]
[15] A coating film comprising a cured product of the aqueous resin composition described in any one of [1] to
[14] .
[0051] The third aspect of the present invention provides the manufacturing method described below.
[0052]
[16] A method for manufacturing a coating film includes a mixing step of preparing an aqueous resin composition as described in any one of [1] to
[14] by mixing an aqueous resin emulsion (α), a curing agent (β) and a curing accelerator (γ); and a coating step of applying the aqueous resin composition to a surface to be coated.
[0053] The manufacturing method of the third aspect of the present invention preferably has the following characteristics.
[0054]
[17] According to the method for manufacturing a coating film as described in
[16] , the coating process is completed within 1 hour after the mixing process is completed.
[0055] The fourth aspect of the present invention provides a kit of aqueous resin compositions as described below.
[0056]
[18] A waterborne resin composition kit, wherein the constituent components of the waterborne resin composition described in any one of [1] to
[14] are separated into a first liquid and a second liquid for storage.
[0057] The first liquid comprises the aqueous resin emulsion (α).
[0058] The second liquid contains the curing agent (β) and the curing accelerator (γ).
[0059] Invention Effects
[0060] According to the present invention, an aqueous resin composition and an aqueous resin composition kit can be provided, which can be cured by short-time curing at room temperature to form a coating film with excellent initial water resistance and can obtain a coating film with good humid heat adhesion to metal materials.
[0061] Furthermore, according to the present invention, a coating film consisting of a cured product of the aqueous resin composition of the present invention can be provided, which has good initial water resistance and good wet and hot adhesion to metal materials.
[0062] In addition, according to the present invention, a method for manufacturing a coating film can be provided, which forms a coating film composed of a cured product of the aqueous resin composition of the present invention. Detailed Implementation
[0063] Hereinafter, preferred examples of the aqueous resin composition, coating film, method for manufacturing the coating film, and aqueous resin composition kit of the present invention will be described in detail.
[0064] It should be noted that the present invention is not limited to the embodiments shown below. For example, additions, omissions, substitutions, and modifications can be made to the number, type, position, quantity, ratio, material, structure, etc., without departing from the purpose of the present invention.
[0065] The following statements used in this specification are explained here.
[0066] "(Meth)acrylate" refers to acrylate or methacrylate. Additionally, "(meth)acrylic acid" refers to acrylic acid or methacrylic acid.
[0067] "Alkenyl unsaturated bond" refers to a double bond between carbon atoms other than the carbon atoms that form the aromatic ring.
[0068] "Weight-average molecular weight" refers to the converted value of standard polystyrene determined by gel permeation chromatography (GPC).
[0069] In polymers using compounds having olefinic unsaturated bonds, the aforementioned structural unit derived from the compound with olefinic unsaturated bonds can refer to a unit in the compound whose chemical structure, excluding the olefinic unsaturated bond, is identical to the chemical structure of the portion of the aforementioned structural unit in the polymer other than the portion corresponding to the olefinic unsaturated bond. The olefinic unsaturated bond in the aforementioned compound can be converted to a single bond during polymer formation. For example, in polymers of methyl methacrylate, the structural unit derived from methyl methacrylate is represented by -CH2-C(CH3)(COOCH3)-.
[0070] It should be noted that in the case of polymers containing compounds with ionic functional groups and olefinically unsaturated bonds, such as structural units (b) derived from olefinically unsaturated carboxylic acids (B) as described later, structural units with ionic functional groups such as carboxyl groups may or may not undergo ion exchange and can be considered as structural units derived from the same ionic compound. For example, the structural unit represented by -CH2-C(CH3)(COONa)- can also be considered as a structural unit derived from methacrylic acid.
[0071] Furthermore, for compounds with multiple independent olefinic unsaturated bonds, more than one olefinic unsaturated bond may remain within the structural unit of the polymer of the aforementioned compound. Multiple independent olefinic unsaturated bonds can refer to multiple olefinic unsaturated bonds that do not form conjugated dienes with each other. For example, in the case of polymers of divinylbenzene, the structural unit derived from divinylbenzene can be a structure without olefinic unsaturated bonds (a form in which both portions of divinylbenzene corresponding to the two olefinic unsaturated bonds are introduced into the polymer chain), or a structure with one olefinic unsaturated bond (a form in which only the portion corresponding to one olefinic unsaturated bond is introduced into the polymer chain).
[0072] "Cure" refers to the process by which molecules in a raw material bond together through a chemical reaction to form a network structure in a polymer.
[0073] "Coating" refers to a substance formed by curing the resin components contained in the aqueous resin composition of this embodiment, and obtained by methods such as applying the aqueous resin composition to the surface to be coated and drying the medium, which forms an integral part with the surface to be coated.
[0074] "Film" refers to a film formed by curing a cured product made by curing the resin components contained in the aqueous resin composition of this embodiment onto a substrate and then peeling it off from the substrate after curing.
[0075] <Waterborne Resin Composition>
[0076] The aqueous resin composition of this embodiment comprises an aqueous resin emulsion (α), a curing agent (β), and a curing accelerator (γ). As described below, the aqueous resin composition of this embodiment is manufactured by mixing the aqueous resin emulsion (α), the curing agent (β), and the curing accelerator (γ).
[0077] [1-1. Aqueous resin emulsion (α)]
[0078] The aqueous resin emulsion (α) comprises a copolymer (X), a polyepoxide compound (Y) without olefinic unsaturated bonds and having two or more epoxy groups per molecule, and an aqueous medium (Z). The aqueous resin emulsion (α) is formed by emulsion polymerization of monomers that form the structural units of the copolymer (X) in the presence of the polyepoxide compound (Y) in an aqueous medium (Z). The aqueous resin emulsion (α) is then mixed with a curing agent (β) and a curing accelerator (γ), described later, and cured to form a cured product with high strength and high elongation.
[0079] <1-1-1. Copolymer (X)>
[0080] The copolymer (X) has a structural unit (a) derived from (meth)acrylate (A) and a structural unit (b) derived from an olefinic unsaturated carboxylic acid (B). The structural unit (a) derived from (meth)acrylate (A) includes a structural unit (a1) derived from a hydrophilic (meth)acrylate (A1).
[0081] Copolymer (X) can be a copolymer composed of structural units (a) and structural units (b) (designated as copolymer (X1)). Copolymer (X) can also be a copolymer having structural units (a), structural units (b), and structural units (c) derived from an olefinically unsaturated aromatic compound (C) having a benzene ring and olefinically unsaturated bonds (designated as copolymer (X2)). Copolymer (X2) can also be composed only of structural units (a) to (c). Copolymer (X) can have structural units (d) other than structural units (a) to (c) (designated as structural units derived from other monomers (D)).
[0082] The amount of copolymer (X) contained in the aqueous resin emulsion (α) can be arbitrarily selected, but is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, relative to the total amount of the aqueous resin emulsion (α). The amount of copolymer (X) contained in the aqueous resin emulsion (α) can be arbitrarily selected, but is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less, relative to the total amount of the aqueous resin emulsion (α). However, it is not limited to these examples.
[0083] The content of copolymer (X) is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 65% by mass or more, relative to the total amount of copolymer (X) and the polyepoxide compound (Y) described later. The content of copolymer (X) is preferably 99% by mass or less, more preferably 94% by mass or less, and even more preferably 88% by mass or less, relative to the total amount of copolymer (X) and the polyepoxide compound (Y) described later.
[0084] [(Meth)acrylate (A)]
[0085] As for (meth)acrylate (A), it is preferable to include an alkyl (meth)acrylate, and more preferably, it is composed of an alkyl (meth)acrylate. Examples of alkyl (meth)acrylates are more preferably alkyl (meth)acrylates having a straight-chain, branched, or cyclic alkyl group having 1 to 18 carbon atoms. Specific examples include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate. Only one type may be used, or two or more types may be used in combination.
[0086] In the example of (meth)acrylate (A), the example of hydrophilic (meth)acrylate (A1) described later may also be included.
[0087] (Meth)acrylates having carboxyl groups are not included in (meth)acrylates (A), but are included in olefinic unsaturated carboxylic acids (B) described later.
[0088] As (meth)acrylate (A), it is preferable to include compounds with low hydrophilicity. This is to improve the rust resistance of the coating film formed by the cured aqueous resin composition of this embodiment. For the same reason, as (meth)acrylate (A), it may contain (meth)acrylates having epoxy groups.
[0089] Examples of epoxy-containing (meth)acrylates include glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, 3,4-epoxycyclohexyl methyl (meth)acrylate, 3,4-epoxycyclohexyl ethyl (meth)acrylate, and 3,4-epoxycyclohexyl propyl (meth)acrylate.
[0090] Structural unit (a) may contain structural units derived from only one of these compounds, or it may contain structural units derived from two or more compounds. Moreover, in these compounds, structural unit (a) preferably contains structural units derived from glycidyl (meth)acrylate.
[0091] Furthermore, (meth)acrylate (A) can be a (meth)acrylate that is neither an alkyl (meth)acrylate nor a compound having an epoxy group. Examples of such (meth)acrylates include (meth)acrylates having hydroxyl groups.
[0092] Examples of hydroxyl-containing (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 12-hydroxylaurate (meth)acrylate, mono(meth)acrylates of polyethylene glycol, and mono(meth)acrylates of polypropylene glycol, etc. These hydroxyl-containing (meth)acrylates can be used in single-component or in combination of two or more types.
[0093] The content of structural unit (a) derived from (meth)acrylate (A) is 20% by mass or more relative to the total amount of copolymer (X) and polyepoxide (Y). This is because, in the method for manufacturing the aqueous resin emulsion (α) described later, the dispersibility of the monomer of copolymer (X) and polyepoxide (Y) can be improved. Considering this, the content of structural unit (a) derived from (meth)acrylate (A) relative to the total amount of copolymer (X) and polyepoxide (Y) is preferably 35% by mass or more, more preferably 45% by mass or more, and even more preferably 60% by mass or more.
[0094] In this embodiment, the percentage of structural units derived from the compound contained in the copolymer can refer to a value calculated based on the mass of the compound used as a raw material for the copolymer. Specifically, for example, the percentage of structural units (a) derived from (meth)acrylate (A) relative to the total amount of copolymer (X) and polyepoxide compound (Y) can refer to the ratio (mass %) of the mass of (meth)acrylate (A) used in the manufacture of copolymer (X) to the total amount mentioned above.
[0095] When the copolymer (X) is composed of structural units (a) and structural units (b), i.e., when it is copolymer (X1), the following ratio is preferred from the viewpoint of improving the dispersibility of the monomers and polyepoxides (Y) forming the copolymer (X1). That is, relative to the total amount of copolymer (X1) and polyepoxides (Y), the content of structural units (a) derived from (meth)acrylate (A) is further preferably 50% by mass or more, and particularly preferably 60% by mass or more.
[0096] The content of structural unit (a) derived from (meth)acrylate (A) is 98% by mass or less relative to the total amount of copolymer (X) and polyepoxide (Y). This is because when it exceeds 98% by mass, there is a tendency for the dispersibility of the aqueous resin emulsion (α) to decrease. Considering this, the content of structural unit (a) derived from (meth)acrylate (A) relative to the total amount of copolymer (X) and polyepoxide (Y) is preferably 92% by mass or less, more preferably 87% by mass or less.
[0097] When the copolymer (X) has structural units (a), (b), and (c), that is, when the copolymer (X) is copolymer (X2), there is a tendency for the dispersibility of the aqueous resin emulsion (α) to decrease. Therefore, the following ratio is preferred. The content of structural unit (a) derived from (meth)acrylate (A) in the copolymer (X2) is further preferably 75% by mass or less, and particularly preferably 65% by mass or less.
[0098] [Hydrophilic (meth)acrylate (A1)]
[0099] The structural units derived from (meth)acrylate (A) include structural units derived from hydrophilic (meth)acrylate (A1).
[0100] Hydrophilic (meth)acrylates (A1) are (meth)acrylates containing a (meth)acryloyloxy group (CH2=CR-COO-, R represents hydrogen or methyl) and derived from an alcohol, i.e., the portion other than the (meth)acryloyloxy group has 2 or fewer carbon atoms. The number of carbon atoms in the portion other than the acryloyloxy group can be, for example, 1 or 2.
[0101] Examples of hydrophilic (meth)acrylates (A1) include methyl (meth)acrylate, ethyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate. The hydrophilic (meth)acrylate (A1) is preferably an alkyl (meth)acrylate derived from an alcohol having 2 or fewer carbon atoms, and more preferably methyl methacrylate.
[0102] The content of structural units (a1) derived from hydrophilic (meth)acrylate (A1) is 15% by mass or more relative to the total amount of copolymer (X) and polyepoxide (Y). This is because if the content of structural units (a1) derived from hydrophilic (meth)acrylate (A1) is less than 15% by mass, gelation will proceed rapidly by mixing the aqueous resin emulsion (α), the curing agent (β) containing aromatic polyamine, and the curing accelerator (γ).
[0103] The content of structural units (a1) derived from hydrophilic (meth)acrylate (A1) is 15% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, relative to the total amount of copolymer (X) and polyepoxide (Y). This is to further improve the water resistance and rust prevention of the coating film formed by the cured product of the aqueous resin composition of this embodiment. The content of structural units (a1) can be 45% by mass or more or 50% by mass or more.
[0104] The upper limit of the content of structural unit (a1) derived from hydrophilic (meth)acrylate (A1) relative to the total amount of copolymer (X) and polyepoxide (Y) is the same as the upper limit of the content of structural unit (a) derived from (meth)acrylate (A). That is, the above-mentioned upper limit is 98% by mass or less, preferably 92% by mass or less, and more preferably 87% by mass or less.
[0105] However, when the polyepoxide compound (Y) described later is a hydrophobic compound such as a bisphenol type epoxy compound, a hydrogenated bisphenol type epoxy compound, or a phenolic varnish type epoxy compound, the proportion of structural unit (a1) in structural unit (a) is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, and particularly preferably 60% by mass or less. This is to improve the affinity between the copolymer (X) and the polyepoxide compound (Y).
[0106] [Alkene unsaturated carboxylic acids (B)]
[0107] The olefinically unsaturated carboxylic acid (B) is a compound having an olefinically unsaturated bond and a carboxyl group. Preferably, the olefinically unsaturated carboxylic acid (B) comprises at least one of the following: α,β-unsaturated monocarboxylic acid, α,β-unsaturated dicarboxylic acid, monoalkyl esters of α,β-unsaturated dicarboxylic acid, and vinyl compounds containing a carboxyl group. Examples of α,β-unsaturated monocarboxylic acids or dicarboxylic acids include, for example, acrylic acid, methacrylic acid, crotonic acid, citraconic acid, itaconic acid, maleic acid, maleic anhydride, fumaric acid, etc. Examples of vinyl compounds containing a carboxyl group include, for example, monohydroxyethyl (meth)acrylate phthalate, monohydroxypropyl (meth)acrylate oxalate, etc.
[0108] Structural unit (b) may be a structural unit derived from only one of these compounds, or it may contain structural units derived from two or more compounds. Among these compounds, as an olefinic unsaturated carboxylic acid (B), it is preferable to include compounds having both (meth)acryloyl and carboxyl groups, or to consist only of compounds having both (meth)acryloyl and carboxyl groups. As an olefinic unsaturated carboxylic acid (B), it is also preferable to include (meth)acrylic acid, or to consist only of (meth)acrylic acid. Structural unit (b) preferably contains only structural units derived from compounds having both (meth)acryloyl and carboxyl groups, and is also preferably composed of structural units derived from (meth)acrylic acid.
[0109] The content of structural units (b) derived from olefinic unsaturated carboxylic acids (B) is 0.1% by mass or more relative to the total amount of copolymer (X) and polyepoxide (Y). This is to improve the dispersibility of the aqueous resin emulsion (α). From this perspective, the content of structural units (b) derived from olefinic unsaturated carboxylic acids (B) relative to the total amount of copolymer (X) and polyepoxide (Y) is preferably 0.3% by mass or more, more preferably 0.5% by mass or more. The content of structural units (b) can be 0.8% by mass or more, or 1.0% by mass or more.
[0110] The content of structural units (b) derived from olefinic unsaturated carboxylic acids (B) is 10% by mass or less relative to the total amount of copolymer (X) and polyepoxide (Y). This is to prevent copolymer (X) from becoming gelled at high temperatures and to improve the high-temperature stability of the aqueous resin emulsion (α). From this perspective, the content of structural units (b) derived from olefinic unsaturated carboxylic acids (B) relative to the total amount of copolymer (X) and polyepoxide (Y) is preferably 7% by mass or less, more preferably 5% by mass or less. The content of structural units (b) can be 4% by mass or less, or 3% by mass or less.
[0111] It should be noted that, relative to the total amount of copolymer (X), the content of structural units (b) derived from olefinic unsaturated carboxylic acids (B) is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and even more preferably 0.8% by mass or more. Relative to the total amount of copolymer (X), the content of structural units (b) derived from olefinic unsaturated carboxylic acids (B) is preferably 12% by mass or less, more preferably 8% by mass or less, even more preferably 5% by mass or less, and particularly preferably 3% by mass or less.
[0112] [Alkene unsaturated aromatic compounds (C)]
[0113] The olefinic unsaturated aromatic compound (C) is a compound that is not a (meth)acrylate (A) or an olefinic unsaturated carboxylic acid (B), and has a benzene ring and an olefinic unsaturated bond. The olefinic unsaturated aromatic compound (C) is preferably an aromatic vinyl compound.
[0114] Examples of aromatic vinyl compounds (C) that are olefinically unsaturated aromatic compounds include styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 4-tert-butylstyrene, tert-butoxystyrene, vinyltoluene, divinyltoluene, vinylnaphthalene, monochlorostyrene, dichlorostyrene, monobromostyrene, dibromostyrene, tribromostyrene, fluorostyrene, styrene sulfonic acid and its salts, α-methylstyrene sulfonic acid and its salts, p-hydroxystyrene, m-hydroxystyrene, o-hydroxystyrene, p-isopropenylphenol, m-isopropenylphenol, and o-isopropenylphenol. The structural unit (c) may be derived from only one of these compounds, or it may contain structural units derived from two or more compounds. More preferably, the structural unit (c) contains a structural unit derived from a hydrocarbon, and particularly preferably, a structural unit derived from styrene.
[0115] When the copolymer (X) contains a structural unit (c) derived from an olefinically unsaturated aromatic compound (C), i.e., when the copolymer (X) is copolymer (X2), the content of the structural unit (c) relative to the total amount of copolymer (X2) and polyepoxide compound (Y) is preferably 5% by mass or more. This is to improve the water resistance of the coating film formed by the cured product of the aqueous resin composition of this embodiment. From this perspective, the content of the structural unit (c) relative to the total amount of copolymer (X2) and polyepoxide compound (Y) is more preferably 10% by mass or more, and even more preferably 15% by mass or more. The content of the structural unit (c) can be 18% by mass or more, 20% by mass or more, or 23% by mass or more.
[0116] When copolymer (X) is copolymer (X2), the content of structural unit (c) relative to the total amount of copolymer (X2) and polyepoxide compound (Y) is preferably 50% by mass or less. This is to improve the weather resistance of the coating film formed by the cured product of the aqueous resin composition of this embodiment. From this perspective, the content of structural unit (c) relative to the total amount of copolymer (X2) and polyepoxide compound (Y) is more preferably 40% by mass or less, and even more preferably 35% by mass or less. The content of structural unit (c) can be 33% by mass or less, 30% by mass or less, or 28% by mass or less.
[0117] The content of structural unit (c) relative to the total amount of copolymer (X2) is preferably 5% by mass or more, more preferably 15% by mass or more, and even more preferably 25% by mass or more. The content of structural unit (c) relative to the total amount of copolymer (X2) is preferably 55% by mass or less, more preferably 45% by mass or less, and even more preferably 35% by mass or less.
[0118] [Other monomers (D)]
[0119] Other monomers (D) are compounds that do not belong to any of (meth)acrylates (A), olefinic unsaturated carboxylic acids (B), and olefinic unsaturated aromatic compounds (C), and have olefinic unsaturated bonds that enable copolymerization with compounds used in the synthesis of copolymers (X).
[0120] Other monomers (D) include, for example, conjugated diene compounds, maleimide compounds, vinyl ether compounds, allyl ether compounds, dialkyl esters of unsaturated dicarboxylic acids, vinyl compounds with cyano groups, etc.
[0121] Examples of the aforementioned conjugated diene compounds include, for example, 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, and chlorobutadiene (2-chloro-1,3-butadiene). These conjugated diene compounds may be used individually or in combination of two or more.
[0122] Examples of the aforementioned maleimide compounds include, for instance, maleimide, N-methylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-dodecylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-benzylmaleimide, N-(4-hydroxyphenyl)maleimide, N-naphthylmaleimide, and N-cyclohexylmaleimide. These maleimide compounds may be used individually or in combination of two or more.
[0123] Examples of the aforementioned vinyl ether compounds include, for instance, alkyl vinyl ethers such as methyl vinyl ether or ethyl vinyl ether, and hydroxyl-containing alkyl vinyl ethers in which some hydrogen atoms are replaced by hydroxyl groups.
[0124] Examples of the aforementioned allyl ether compounds include, for example, allyl alkyl ethers such as allyl methyl ether or allyl ethyl ether, hydroxyl-containing allyl alkyl ethers in which some hydrogen atoms are replaced by hydroxyl groups, and allyl glycidyl ethers.
[0125] Examples of dialkyl esters of the aforementioned unsaturated dicarboxylic acids include, for example, maleic acid, fumaric acid, itaconic acid, citraconic acid, mesoconic acid, maleic anhydride, itaconic anhydride, citraconic anhydride, and tetrahydrophthalic anhydride. These dialkyl esters of unsaturated dicarboxylic acids may be used individually or in combination of two or more.
[0126] Examples of the aforementioned vinyl compounds containing a cyano group include acrylonitrile, methacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-chloroacrylonitrile, and α-fluoroacrylonitrile. Only one of these cyano-containing vinyl monomers may be used, or two or more may be used in combination.
[0127] <1-1-2. Polyepoxides (Y)>
[0128] Polyepoxides (Y) are compounds that do not have olefinic unsaturated bonds and have more than two epoxy groups per molecule.
[0129] The polyepoxide compound (Y) is preferably selected from at least one of bisphenol type epoxy compounds, hydrogenated bisphenol type epoxy compounds, diglycidyl ether, triglycidyl ether, tetraglycidyl ether, diglycidyl ester, triglycidyl ester and tetraglycidyl ester.
[0130] Examples of compounds having two or more epoxy groups per molecule include diglycidyl ether of bisphenol A, diglycidyl ether of hydrogenated bisphenol A, diglycidyl ether of bisphenol F, diglycidyl ether of hydrogenated bisphenol F, glycerol polyglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, diglycidyl ester of phthalic acid, 1,4-cyclohexanediethanol diglycidyl ether, 1,3-cyclohexanediethanol diglycidyl ether, and diglycidyl ester of hexahydrophthalic acid. A compound may contain one or more of these compounds.
[0131] The aforementioned polyepoxide compound (Y) is more preferably a bisphenol-type epoxy compound or a hydrogenated bisphenol-type epoxy compound, and even more preferably a bisphenol A-type epoxy compound or a hydrogenated bisphenol A-type epoxy compound, and even more preferably a bisphenol A-type epoxy compound. This is to further improve the water resistance and rust prevention of the coating film formed by the cured product of the waterborne resin composition of this embodiment.
[0132] The weight-average molecular weight of the polyepoxide compound (Y) is not particularly limited, but is preferably 1000 or less, more preferably 800 or less, and even more preferably 500 or less. Improved compatibility between the polyepoxide compound (Y) and the copolymer (X) allows for the preparation of an aqueous resin emulsion (α) with excellent dispersibility and storage stability. The lower limit of the weight-average molecular weight of the polyepoxide compound (Y) can be arbitrarily chosen, for example, 200 or 300, but is not limited to these values.
[0133] The epoxy equivalent (mass of the polyepoxide compound (Y) corresponding to 1 mol of epoxy groups) of the polyepoxide compound (Y) is preferably 500 g / mol or less, more preferably 350 g / mol or less, further preferably 250 g / mol or less, and particularly preferably 200 g / mol or less. This is to improve the strength of the film formed by the cured product of the aqueous resin composition of this embodiment.
[0134] The lower limit of the epoxy equivalent can be chosen arbitrarily, for example, it can be above 70 g / mol or above 120 g / mol, but it is not limited to these examples.
[0135] The content of the polyepoxide compound (Y) relative to the total amount of copolymer (X) and polyepoxide compound (Y) is 1% by mass or more. This is because a coating with excellent rust-preventive properties can be obtained by curing the aqueous resin composition. From this perspective, the content of the polyepoxide compound (Y) relative to the total amount of copolymer (X) and polyepoxide compound (Y) is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more. It can be 12% by mass or more, or 20% by mass or more, depending on the need.
[0136] The content of the polyepoxide compound (Y) relative to the total amount of the copolymer (X) and the polyepoxide compound (Y) is 40% by mass or less. This is to obtain an aqueous resin emulsion (α) with high dispersibility. From this perspective, the content of the polyepoxide compound (Y) relative to the total amount of the copolymer (X) and the polyepoxide compound (Y) is preferably 35% by mass or less, more preferably 30% by mass or less.
[0137] The amount of polyepoxide compound (Y) contained in the aqueous resin emulsion (α) is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 4% by mass or more, relative to the total amount of the aqueous resin emulsion (α). The amount of polyepoxide compound (Y) contained in the aqueous resin emulsion (α) is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, relative to the total amount of the aqueous resin emulsion (α).
[0138] <1-1-3. Aqueous Medium (Z)>
[0139] The aqueous medium (Z) can be chosen arbitrarily, but water is preferred. However, as long as the dispersibility of the copolymer (X) and the polyepoxide compound (Y) is not impaired, a substance formed by adding a water-soluble solvent to water can also be used as the aqueous medium (Z). The hydrophilic (water-soluble) solvent added to the water can be chosen arbitrarily, such as methanol, ethanol, and N-methylpyrrolidone.
[0140] The amount of aqueous medium (Z) in the aqueous resin emulsion (α) can be selected as needed, preferably at a concentration of 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more. The amount of aqueous medium (Z) in the aqueous resin emulsion (α) can be selected as needed, preferably at 80% by mass or less, more preferably at 70% by mass or less. The concentration of non-volatile components in the aqueous resin emulsion (α) can be 50-70% by mass or 55-65% by mass.
[0141] <1-1-4. Manufacturing method of aqueous resin emulsion (α)>
[0142] The method for manufacturing the aqueous resin emulsion (α) described in this embodiment can be carried out by emulsion polymerization of a monomer containing (meth)acrylate (A) and olefinic unsaturated carboxylic acid (B) (i.e., the monomer used to form the copolymer (X)) in an aqueous medium (Z) in the presence of a polyepoxide compound (Y).
[0143] The percentage of each raw material in the total raw material used to manufacture the aqueous resin emulsion (α) is the same as the percentage of the structural unit derived from the raw material or the compound corresponding to the raw material in the aqueous resin emulsion (α).
[0144] As an emulsion polymerization method in the method for manufacturing the aqueous resin emulsion (α) of this embodiment, methods such as adding all components containing monomers together or continuously supplying each component while performing polymerization can be used. Stirring is preferred during the polymerization reaction.
[0145] Emulsion polymerization is preferably carried out at any chosen temperature, for example, 30–90°C, more preferably at 40–80°C, and even more preferably at 40–70°C. This is to suppress the reaction between the carboxyl groups contained in the monomer and the epoxy groups contained in the polyepoxide compound (Y).
[0146] Emulsifiers can be used in emulsion polymerization. The emulsifiers used can be chosen arbitrarily, and examples include nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene fatty acid esters, and polyoxyethylene sorbitan fatty acid esters; and anionic surfactants such as alkyl sulfate salts, alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, polyoxyethylene alkyl sulfates, and polyoxyethylene alkyl phosphates. They can be used alone or in combination of two or more. Alkylbenzene sulfonates are preferred as emulsifiers, and sodium dodecylbenzene sulfonate is more preferred.
[0147] In emulsion polymerization, polymerization initiators are preferred. Peroxides are preferred, for example. Examples of peroxides used as polymerization initiators include potassium persulfate, ammonium persulfate, and hydrogen peroxide. Alternatively, redox initiators based on the combined use of peroxides and reducing agents can also be used. Examples of reducing agents include sodium formaldehyde sulfoxylate, ascorbic acid, sulfites, tartaric acid, or their salts. Furthermore, alcohols and thiols can be used as chain transfer agents as needed.
[0148] According to the method for manufacturing the aqueous resin emulsion (α) of this embodiment, an aqueous resin emulsion (α) in which a polyepoxide compound (Y) is uniformly dispersed in the particles of the generated copolymer (X) can be obtained.
[0149] Here, "uniform dispersion" does not necessarily require that the copolymer (X) and the polyepoxide (Y) be compatible. It is sufficient that the polyepoxide (Y) is present unbiasedly on either the central side or the surface side of the copolymer (X) particles.
[0150] <1-1-5. Characteristics of Aqueous Resin Emulsions (α)>
[0151] [pH of aqueous resin emulsion (α)]
[0152] The pH of the aqueous resin emulsion (α) is preferably 2 to 10, more preferably 5 to 9. A pH within this range improves the mechanical and chemical stability of the aqueous resin emulsion (α). The pH is measured at 25°C using a pH meter based on a hydrogen ion concentration indicator with a glass electrode as the standard electrode. For example, the pH can be adjusted by adding an alkaline substance to the aqueous resin emulsion (α) during or after emulsion polymerization. Examples of alkaline substances used for pH adjustment include ammonia, triethylamine, ethanolamine, and caustic soda. One or more of these substances can be used alone or in combination.
[0153] [Concentration of non-volatile components in aqueous resin emulsion (α)]
[0154] The concentration of non-volatile components in the aqueous resin emulsion (α) is preferably 10–65% by mass, more preferably 15–60% by mass, and even more preferably 20–55% by mass. The above-mentioned concentration of non-volatile components can be 30–50% by mass or 35–45% by mass. The concentration of non-volatile components in the aqueous resin emulsion (α) can be appropriately determined considering the workability in the mixing process of the aqueous resin emulsion (α) with the curing agent (β) and curing accelerator (γ), or in the coating process of the aqueous resin composition. The concentration of non-volatile components in the aqueous resin emulsion (α) can be appropriately adjusted by adjusting the amount of aqueous medium (Z) added.
[0155] It should be noted that the concentration of non-volatile components in the aqueous resin emulsion (α) is determined using the method shown below. 1 g of the aqueous resin emulsion (α) is weighed into a 5 cm diameter aluminum pan and dried at 105°C for 1 hour under atmospheric pressure and air circulation in a desiccator. The mass of the remaining components is then measured. The ratio (mass%) of the measured residual component to the mass of the aqueous resin emulsion (α) before drying is taken as the concentration of non-volatile components in the aqueous resin emulsion (α).
[0156] [Viscosity of aqueous resin emulsion (α)]
[0157] In this embodiment, the viscosity of the aqueous resin emulsion (α) is measured at 23°C. The viscosity of the aqueous resin emulsion (α) is measured using a Type B viscometer, with the measured value taken at a rotation speed of 60 rpm using a rotor corresponding to the viscosity of the aqueous resin emulsion. For example, when the viscosity of the aqueous resin emulsion (α) is approximately several mPa·s to several hundred mPa·s, rotor No. 1 is used for measurement. For example, the viscosity can be 0.1–300 mPa·s, 1–100 mPa·s, 3–50 mPa·s, or 5–25 mPa·s.
[0158] [Glass transition temperature of copolymer (X)]
[0159] The glass transition temperature (Tg) of copolymer (X) is calculated based on the glass transition temperatures of the homopolymers of the monomers used in the synthesis of copolymer (X). The specific method for calculating the glass transition temperature (Tg) of copolymer (X) involves using monomer M, which is used as a raw material. i The glass transition temperature Tg of the homopolymer (i = 1, 2, 3, ...) i The mass fraction X of monomer i in all monomers i (ΣX i (Total monomers) = 1), calculated using the following formula (1). Formula (1), Tg and Tg i All calculations are based on absolute temperature (K).
[0160] 1 / Tg=Σ(X i / Tg i …(1)
[0161] The glass transition temperature of the homopolymer used in the Tg calculation is the value recorded in known sources. Specifically, the values are listed in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). For monomers for which multiple values are recorded in the aforementioned Polymer Handbook, the highest value is used.
[0162] The glass transition temperature (Tg) of copolymer (X) is preferably -30°C (243K) or higher. This is to improve the strength of the film formed by the cured product of the aqueous resin composition of this embodiment. From this perspective, the glass transition temperature (Tg) of copolymer (X) is more preferably -10°C (263K) or higher, and even more preferably 0°C (273K) or higher. The glass transition temperature (Tg) of copolymer (X) can be 5°C or higher or 10°C or higher. The glass transition temperature (Tg) of copolymer (X) is preferably 100°C (373K) or lower, and more preferably 80°C (353K) or lower. This is to improve the adhesion of the coating film formed by the cured product of the aqueous resin composition of this embodiment to the substrate. From this perspective, the glass transition temperature (Tg) of copolymer (X) is further preferably 60°C (333K) or lower, and particularly preferably 50°C (323K) or lower. This is because, within such a range, the flexibility of the coating film formed by the cured product of the aqueous resin composition of this embodiment can be improved. The glass transition temperature (Tg) of copolymer (X) can be below 40°C or below 30°C.
[0163] [Epoxy group content in aqueous resin emulsion (α)]
[0164] The epoxy group content in the aqueous resin emulsion (α) is the proportion of the number of moles of epoxy groups contained in 1 g of aqueous resin emulsion (α). The method for determining the amount of epoxy groups N1 [mol / g] contained in 1 g of aqueous resin emulsion (α) is as described in the examples below.
[0165] [The percentage of epoxy groups in the total amount of copolymer (X) and polyepoxide (Y)]
[0166] The polyepoxide compound (Y) contained in the aqueous resin emulsion (α) of this embodiment contains epoxy groups. The epoxy group content in the total amount of copolymer (X) and polyepoxide compound (Y) is preferably 0.50 × 10⁻⁶. -4 mol / g or higher, more preferably 1.0 × 10⁻⁶ -4 mol / g or higher, more preferably 4.0 × 10⁻⁶ -4 mol / g or higher, more preferably 6.0 × 10⁻⁶. -4 mol / g or higher. This is because it can improve the water resistance, rust prevention, and adhesion to the substrate of the coating film formed by the cured product of the aqueous resin composition of this embodiment.
[0167] The preferred percentage of epoxy groups in the total amount of copolymer (X) and polyepoxide (Y) is 50 × 10⁻⁶. -4 Below mol / g, more preferably 30 × 10 -4 Below mol / g, more preferably 20 × 10⁻⁶ -4Below mol / g. The epoxy group content in the total amount of copolymer (X) and polyepoxide (Y) can be 15 × 10⁻⁶. -4 Below mol / g, or 10×10 -4 Below mol / g.
[0168] [Content of epoxy groups in the non-volatile components of aqueous resin emulsion (α)]
[0169] The preferred content of epoxy groups in the non-volatile components of the aqueous resin emulsion (α) is 0.50 × 10⁻⁶. -4 mol / g or higher, more preferably 3.0 × 10⁻⁶ -4 mol / g or higher, more preferably 5.0 × 10⁻⁶ -4 The concentration is mol / g or higher. This is because it can improve the water resistance, rust prevention, and adhesion to the substrate of the coating film formed by the cured product of the aqueous resin composition of this embodiment. The content of epoxy groups in the non-volatile components of the aqueous resin emulsion (α) can be 1.0 × 10⁻⁶. -4 mol / g or higher, or 6.0 × 10 - 4 Above mol / g.
[0170] The preferred content of epoxy groups in the non-volatile components of the aqueous resin emulsion (α) is 50 × 10⁻⁶. -4 Below mol / g, more preferably 30 × 10 -4 Below mol / g, more preferably 20 × 10⁻⁶ -4 Below mol / g. The content of epoxy groups in the non-volatile components of aqueous resin emulsions (α) can be 15 × 10⁻⁶. -4 Below mol / g, or 10×10 -4 Below mol / g.
[0171] The content R of epoxy groups in the non-volatile components of (α) in aqueous resin emulsions EP [mol / g] is the value obtained as follows. The concentration of the non-volatile component of the aqueous resin emulsion (α) is set to C. S [mass %] When the amount of epoxy groups contained in each 1g of aqueous resin emulsion (α) is set as N1 [mol / g], the epoxy group content R EP As shown in equation (2). The method for determining N1 is described below in the embodiments.
[0172] R EP [mol / g]=N1 / (C S / 100)…(2)
[0173] [Carboxyl group content in aqueous resin emulsion (α)]
[0174] The percentage of carboxyl groups in the aqueous resin emulsion (α) is the proportion of the number of moles of carboxyl groups contained in 1 g of the aqueous resin emulsion (α). The method for determining the number of moles of carboxyl groups contained in 1 g of aqueous resin emulsion (α) is as described in the examples below.
[0175] [Carboxyl group content in the total amount of copolymer (X) and polyepoxide (Y)]
[0176] In this embodiment, it is preferred that one or both of the copolymer (X) and the polyepoxide compound (Y) contained in the aqueous resin emulsion (α) contain carboxyl groups, and the copolymer (X) contains carboxyl groups. The carboxyl group content in the total amount of copolymer (X) and polyepoxide compound (Y) is preferably 0.10 × 10⁻⁶. -4 0.50 × 10 mol / g or higher, more preferably 0.50 × 10 -4 mol / g or higher, more preferably 1.0 × 10⁻⁶ -4 The concentration is above mol / g. This is because the aggregation of the copolymer (X) can be inhibited during polymerization and storage of the aqueous resin emulsion (α) after polymerization.
[0177] The preferred content of carboxyl groups in the total amount of copolymer (X) and polyepoxide (Y) is 10 × 10⁻⁶. -4 Below mol / g, more preferably 5.0 × 10⁻⁶ -4 Below mol / g. It can be 3.0 × 10⁻⁶. -4 Below mol / g, it can also be 2.5 × 10⁻⁶. -4 Below mol / g, or 2.0 × 10 -4 Below mol / g.
[0178] [The content of carboxyl groups in the non-volatile components of aqueous resin emulsion (α)]
[0179] The preferred content of carboxyl groups in the non-volatile components of the aqueous resin emulsion (α) is 0.10 × 10⁻⁶. -4 0.50 × 10 mol / g or higher, more preferably 0.50 × 10 -4 mol / g or higher, more preferably 1.0 × 10⁻⁶ -4 The concentration is above mol / g. This is because the aggregation of the copolymer (X) can be inhibited during polymerization and storage of the aqueous resin emulsion (α) after polymerization.
[0180] The preferred content of carboxyl groups in the non-volatile components of the aqueous resin emulsion (α) is 10 × 10⁻⁶. -4 Below mol / g, more preferably 5.0 × 10⁻⁶ -4 Below mol / g. It can be 3.0 × 10⁻⁶. -4 Below mol / g, it can also be 2.5 × 10⁻⁶. -4Below mol / g, or 2.0 × 10 -4 Below mol / g.
[0181] Here, the carboxyl group mentioned above refers not only to -COOH, but also to cations other than hydrogen ions and -COO. - The structure formed by the combination. The content of carboxyl groups in the non-volatile components of the aqueous resin emulsion (α) is calculated as shown in the following formula, by subtracting the reduction in the amount of functional groups that react with carboxyl groups in the raw materials before and after polymerization from the carboxyl group content in the raw materials. The raw materials mentioned above refer to the components used in the synthesis of the aqueous resin emulsion (α). In addition, in this invention, the functional group that reacts with carboxyl groups refers to the epoxy group, and hydroxyl groups are not considered as functional groups that react with carboxyl groups.
[0182] The following is a description of the carboxyl group content R in the non-volatile components of the aqueous resin emulsion (α). CX The method for determining [mol / g] is explained in detail. The total amount of carboxyl groups in the raw materials (including initiators, solvents, and other additives) is set as N3; the total amount of epoxy groups in the raw materials (including initiators, solvents, and other additives) is set as N2; and the amount of epoxy groups contained in each 1g of aqueous resin emulsion (α) is set as N1 [mol / g]. The concentration of non-volatile components in the aqueous resin emulsion (α) is set as C. S [mass %]. At this point, the carboxyl group content R CX As shown in equation (3). The methods for determining N1 and N2 are described later in the embodiments. N2 can be obtained by calculation.
[0183] R CX [mol / g]={N3-(N2-N1)} / (C S / 100)…(3)
[0184] [1-2. Curing agent (β)]
[0185] The curing agent (β) contains an aromatic polyamine (F) with active hydrogen that is reactive to the epoxy group. Here, active hydrogen that is reactive to the epoxy group refers to a hydrogen atom that can be released from the nitrogen atom after the amino group of the aromatic polyamine (F) forms a bond by nucleophilic attack on the epoxy group.
[0186] The amino group of the aromatic polyamine (F) is preferably an unsubstituted amino group (-NH2 (unsubstituted) or an amino group with only one substituent (-NHR (R is a substituent)).
[0187] The aforementioned aromatic polyamines (F) with active hydrogen have a benzene ring and two or more amino groups per molecule. Aromatic polyamines (F) with active hydrogen can be compounds with only one type of amino group or compounds with two or more types of amino groups.
[0188] The curing agent (β) may contain only one of the above-mentioned aromatic polyamines (F) with active hydrogen, or it may contain two or more.
[0189] Examples of aromatic polyamines (F) possessing active hydrogen, such as m-phenylenediamine (hereinafter sometimes referred to as "MXDA"), diaminodiphenylmethane, m-phenylenediamine, diaminodiphenyl sulfone, and their modified forms, are as follows. The modified forms are preferably compounds obtained by an addition reaction of atoms or groups bonded to the amino group of MXDA.
[0190] In this embodiment, the curing agent (β) contains the aforementioned aromatic polyamine (F) with active hydrogen, and thus cures by short-term curing at room temperature, resulting in a waterborne resin composition capable of forming a coating film with excellent initial water resistance and humid heat adhesion to metal materials. Therefore, the waterborne resin composition of this embodiment is suitable for anti-corrosion coating of metal products such as iron.
[0191] The reason for this effect is still uncertain, but the curing agent (β) containing the aforementioned aromatic polyamine (F) with active hydrogen can easily penetrate into the particles of the aqueous resin emulsion (α). Therefore, this is believed to be due to the curing-promoting function of the curing agent (β) on the polyepoxide (Y) contained in the aqueous resin emulsion (α), resulting in the rapid curing of the aqueous resin composition.
[0192] Generally, when comparing aromatic compounds with aliphatic compounds of the same molecular weight, aromatic compounds are more hydrophobic. It is speculated that the aforementioned aromatic polyamine (F) containing active hydrogen in the curing agent (β) is more hydrophobic than the aqueous resin emulsion (α). Therefore, it is believed that the aforementioned aromatic polyamine (F) containing active hydrogen is less likely to remain in the aqueous layer of the aqueous resin composition and is more likely to partition into the interior of the particles of the aqueous resin emulsion (α). Consequently, the aforementioned aromatic polyamine (F) containing active hydrogen, for example, compared to aliphatic polyamines of the same molecular weight, more easily penetrates into the interior of the particles of the aqueous resin emulsion (α) and more easily approaches the epoxy groups present in the aqueous resin emulsion (α). As a result, it is believed that the aqueous resin composition of this embodiment containing the aforementioned aromatic polyamine (F) containing active hydrogen is more likely to promote the curing of the polyepoxide compound (Y) contained in the aqueous resin emulsion (α) compared to the case containing aliphatic polyamines of the same molecular weight, and the curing speed of the aqueous resin composition is faster.
[0193] As for the aforementioned aromatic polyamines (F) containing active hydrogen, from the perspective of facilitating the curing reaction of the aqueous resin composition, aromatic polyamines (F) containing two or more benzene rings per molecule are preferred, and aromatic polyamines (F) containing three or more benzene rings per molecule are more preferred. The reason for this effect is not yet certain, but aromatic polyamines (F) containing two or more benzene rings per molecule have higher hydrophobicity compared to aromatic polyamines (F) containing only one benzene ring per molecule. Therefore, aromatic polyamines (F) containing two or more benzene rings per molecule can more easily penetrate the interior of the particles of the aqueous resin emulsion (α), and can more easily approach the epoxy groups of the polyepoxide compound (Y) contained in the aqueous resin emulsion (α) compared to aromatic polyamines (F) containing only one benzene ring per molecule. Thus, it is speculated that the curing-promoting function of the polyepoxide compound (Y) brought by the curing agent (β) can be obtained more effectively, and the curing speed of the aqueous resin composition is accelerated.
[0194] As the aforementioned aromatic polyamine (F) with active hydrogen, from the perspective of water solubility and ease of acquisition, it is preferable to include aromatic polyamine (F) having 13 or fewer benzene rings per molecule, and more preferably to include aromatic polyamine (F) having 10 or fewer benzene rings.
[0195] As aromatic polyamines (F) having two or more benzene rings per molecule, examples include compounds represented by the following general formula (1-1) and compounds represented by the following general formula (1-2), etc.
[0196]
[0197] In equation (1-1), A 2 A 3 Each of these can be used independently to represent 1,2-phenylene, 1,3-phenylene, or 1,4-phenylene. n represents an integer from 1 to 12.
[0198]
[0199] In equation (1-2), A 1 It represents 1,2-phenylene, 1,3-phenylene, or 1,4-phenylene.
[0200] A in equation (1-1) 2 A 3 In equation (1-2), A 1 All represent 1,2-phenylene, 1,3-phenylene, or 1,4-phenylene. For A in formula (1-1) 2 A 3 In equation (1-2), A 1 To facilitate the curing reaction of the waterborne resin composition, it is preferred that all components are 1,3-phenylene.
[0201] In the compound represented by formula (1-1), the A contained in the repeating unit 2 (A in parentheses) 2 A not included in repeating units 3 (A outside the parentheses) 3 The same or different A can be used in the compound represented by formula (1-1). Furthermore, in the compound where n is 2 to 12, the repeating unit contains A. 2 They can be all the same or contain different groups. To facilitate the manufacture of the compound represented by formula (1-1), it is preferable that the compound contains A. 2 A 3 All are the same.
[0202] In formula (1-1), the number of repeating units n, as indicated in parentheses, represents an integer from 1 to 12. Various compounds with different numbers of repeating units (the value of n) in formula (1-1) can be used as the aforementioned aromatic polyamine (F) containing active hydrogen. From the perspective of facilitating the curing reaction of the aqueous resin composition, the value of n in formula (1-1) is preferably 2 or more. Furthermore, to ensure good water solubility and ease of acquisition of the aforementioned aromatic polyamine (F) containing active hydrogen, the value of n in formula (1-1) is preferably 9 or less.
[0203] As for the above-mentioned aromatic polyamine (F) with active hydrogen, from the viewpoint of forming an aqueous resin composition that can form a coating film with superior initial water resistance, the content of the compound in general formula (1-1) where n is 1 is preferably 10% to 35% by mass, more preferably 15% to 30% by mass, and even more preferably 18% to 25% by mass.
[0204] The compound represented by general formula (1-1) exhibits higher hydrophobicity compared to the compound represented by general formula (1-2). Therefore, the compound represented by general formula (1-1) more readily approximates the epoxy groups present in the polyepoxide compound (Y) contained in the aqueous resin emulsion (α). Consequently, in the case where the aromatic polyamine (F) possessing active hydrogen comprises a compound represented by general formula (1-1), an aqueous resin composition capable of forming a coating film with superior initial water resistance is achieved.
[0205] Further preferably, the aromatic polyamine (F) with active hydrogen comprises a compound represented by general formula (1-1) and MXDA. This results in an aqueous resin composition capable of forming a coating film with superior initial water resistance. It is presumably due to the synergistic effect of the high hydrophobicity of the compound represented by general formula (1-1) and the low steric hindrance of MXDA. That is, it is presumably that through this synergistic effect, the aromatic polyamine (F) with active hydrogen more readily approaches the epoxy groups contained in the aqueous resin emulsion (α), further promoting the curing of the polyepoxide compound (Y) contained in the aqueous resin emulsion (α), and accelerating the curing speed of the aqueous resin composition. Furthermore, in the case where the aromatic polyamine (F) with active hydrogen comprises a compound represented by general formula (1-1) and MXDA, the curing of the aqueous resin composition is promoted through the aforementioned synergistic effect, thus enabling the formation of a cured product with higher film yield strength.
[0206] When the aforementioned aromatic polyamine (F) with active hydrogen contains a compound represented by general formula (1-1) and MXDA, the content of MXDA in the aforementioned aromatic polyamine (F) with active hydrogen is preferably 10% to 40% by mass, more preferably 20% to 30% by mass, and even more preferably 24% to 28% by mass. Furthermore, the compound represented by general formula (1-1) in the aforementioned aromatic polyamine (F) with active hydrogen is preferably 60% to 90% by mass, more preferably 70% to 80% by mass, and even more preferably 72% to 76% by mass. This is to make the synergistic effect produced by containing the compound represented by general formula (1-1) and MXDA more significant.
[0207] As the above-mentioned aromatic polyamine (F) with active hydrogen, the content of the compound in general formula (1-1) where n is 1 is preferably 10% to 35% by mass relative to the total amount of the above-mentioned aromatic polyamine (F) with active hydrogen, more preferably 15% to 30% by mass, and even more preferably 18% to 25% by mass.
[0208] Commercially available products can be used as the aforementioned aromatic polyamines (F) containing active hydrogen. Examples of commercially available products containing aromatic polyamines (F) having two or more benzene rings per molecule include Gaskamine 328 (trade name, Mitsubishi Gas Chemical Co., Ltd.) and Gaskamine 240 (trade name, Mitsubishi Gas Chemical Co., Ltd.). Both Gaskamine 328 and Gaskamine 240 are mixtures containing a modified MXDA compound and MXDA. Gaskamine 328 contains a compound represented by general formula (1-1) as a modified MXDA compound. Gaskamine 240 contains a compound represented by general formula (1-2) as a modified MXDA compound.
[0209] More specifically, Gaskamine 328 comprises a compound of formula (1-1) as an aromatic polyamine formed from the reaction of epichlorohydrin and MXDA, and MXDA. Specifically, Gaskamine 328 comprises 73.3% by mass of the compound of formula (1-1) (A in formula (1-1)). 2 and A 3 All are 1,3-phenylene. n is 1 to 12. ). The content of the compound with n=1 among the compounds represented by formula (1-1) contained in Gaskamine 328 is 20.9% by mass. In addition, Gaskamine 328 contains 26.7% by mass of MXDA.
[0210] Gaskamine 240 comprises a compound of formula (1-2) representing an aromatic polyamine formed from the reaction of styrene and MXDA, and MXDA. Specifically, Gaskamine 240 comprises more than 99% by mass of the compound of formula (1-2) (in formula (1-2), A... 1 It is 1,3-phenylene. Additionally, Gaskamine 240 contains less than 1% by mass of MXDA.
[0211] It should be noted that the individual components and their contents of the curing agent (β) contained in the waterborne resin composition can be confirmed using chromatographic analysis such as gas chromatography (GC) and gel filtration chromatography (GPC).
[0212] Regarding the content of the aromatic polyamine (F) containing active hydrogen contained in the curing agent (β), the active hydrogen contained in the aromatic polyamine (F) is 0.10 equivalents or more, preferably 0.20 equivalents or more, and more preferably 0.30 equivalents or more, relative to 1 equivalent of epoxy groups contained in the aqueous resin emulsion (α). This is because by increasing the crosslinking density of the cured aqueous resin composition, the initial water resistance and film yield strength are improved, and by increasing the reactivity rate of the epoxy groups contained in the aqueous resin emulsion (α), the hygrothermal adhesion to metal materials is improved.
[0213] Regarding the content of the aromatic polyamine (F) containing active hydrogen in the curing agent (β), relative to the 1 equivalent of epoxy groups contained in the aqueous resin emulsion (α), the active hydrogen contained in the aromatic polyamine (F) is 1.50 equivalents or less, preferably 1.3 equivalents or less, and more preferably 1.2 equivalents or less. This is because excessive curing shrinkage of the aqueous resin composition can be suppressed, and a cured product with good hygrothermal adhesion to metal materials can be formed.
[0214] [1-3. Curing accelerator (γ)]
[0215] The curing accelerator (γ) functions to promote the curing of the aqueous resin composition and form a film with high yield strength. The curing accelerator (γ) contains a tertiary amine that does not possess active hydrogen that is reactive to epoxy groups. In this embodiment, the tertiary amine is NR. 1 R 2 R 3 (where R is in the formula) 1 R 2 R 3 Substituents can be different individually or can contain two or more identical substituents. R 1 R 2 R 3 Compounds that can bond together to form rings.
[0216] The curing accelerator (γ) is preferably an aliphatic tertiary amine, an alicyclic tertiary amine, a heteroaromatic tertiary amine, or has a curing accelerator that is not directly bonded to the tertiary amine (NR). 1 R 2 R 3 At least one compound of an aromatic tertiary amine containing a nitrogen atom of a phenyl group. This is to enhance the nucleophilicity of the curing accelerator (γ) and effectively carry out the curing reaction.
[0217] Examples of aliphatic tertiary amines include triethylamine, tri-n-propylamine, triisopropylamine, tri-n-butylamine, tri-sec-butylamine, and tri-n-hexylamine.
[0218] Examples of alicyclic tertiary amines include 1,4-diazabicyclo[2.2.2]octane (DABCO), 1,5-diazabicyclo[4.3.0]non-5-ene, and 1,8-diazabicyclo[5.4.0]undec-7-ene.
[0219] As a heteroaromatic tertiary amine, a compound having an imidazole skeleton is preferred, specifically, imidazole, 2-methylimidazolium, 2-ethyl-4-methylimidazolium, etc. can be listed as examples.
[0220] As having a structure not directly bonded to tertiary amines (NR) 1 R 2 R 3 Aromatic tertiary amines with a nitrogen atom in the phenyl group include dimethylbenzylamine, diethylbenzylamine, tribenzylamine, 2,4,6-tris(dimethylamino)methylphenol, and 2-phenylimidazole.
[0221] Among these curing accelerators (γ), compounds described in (i) and / or (ii) below are particularly preferred.
[0222] (i) an alicyclic tertiary amine that does not have an active hydrogen relative to the epoxy group and has a saturated ring structure in which two nitrogen atoms are bonded to each other through three substituents of the amino group.
[0223] (ii) A heteroaromatic tertiary amine that does not have an active hydrogen relative to the epoxy group and has a heteroaromatic ring structure containing two or more nitrogen atoms.
[0224] Examples of (i) alicyclic tertiary amines include 1,4-diazabicyclo[2.2.2]octane (DABCO). Examples of (ii) heteroaromatic tertiary amines include imidazoles.
[0225] One type of curing accelerator (γ) may be used, or two or more may be used in combination.
[0226] The content of the curing accelerator (γ) is 0.0070 mol or more, preferably 0.070 mol or more, more preferably 0.18 mol or more, and even more preferably 0.30 mol or more, relative to the equivalent of epoxy group 1 contained in the aqueous resin emulsion (α). This is because the film formed by the cured product of the aqueous resin composition of this embodiment has a high film yield strength.
[0227] The content of the curing accelerator (γ) is 1.5 mol or less, preferably 1.0 mol or less, more preferably 0.70 mol or less, even more preferably 0.44 mol or less, even more preferably 0.40 mol or less, and particularly preferably 0.38 mol or less, relative to the equivalent of epoxy group 1 contained in the aqueous resin emulsion (α). This is because the cured product of the aqueous resin composition of this embodiment becomes a coating film with good hygrothermal adhesion to metal materials. In addition, when the content of the curing accelerator (γ) is 1.5 mol or less, the short-term gelation of the aqueous resin composition can be suppressed, and a cured product with good rust prevention properties can be obtained.
[0228] [1-4. Other ingredients]
[0229] The aqueous resin composition of this embodiment may contain pigments. Examples of pigments include titanium dioxide, talc, barium sulfate, carbon black, iron oxide, calcium carbonate, silicon dioxide, talc, mica, kaolin, clay, ferrite, and silica sand. The pigment may contain only one compound or two or more compounds. The pigment is preferably present in the aqueous resin composition at 0.1 to 50% by mass, more preferably at 1 to 40% by mass. This is to improve the hiding power of the coating film.
[0230] Aqueous resin compositions may contain additives such as fillers, organic or inorganic hollow spheres, dispersants (e.g., amino alcohols, polycarboxylic acid esters, etc.), surfactants, coupling agents (e.g., silane coupling agents, etc.), defoamers, preservatives (e.g., biocides, fungicides, algicides, and combinations thereof), flow agents, leveling agents, neutralizing agents (e.g., hydroxides, amines, ammonia, carbonates, etc.).
[0231] Silane coupling agents are preferred as coupling agents. Examples of silane coupling agents include epoxy silane compounds. Specific examples include 3-epoxypropoxypropylmethyldimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0232] The amount of silane coupling agent added is preferably 0.1 to 5 parts by weight, more preferably 0.3 to 3 parts by weight, relative to 100 parts by weight of the aqueous resin emulsion. This is to improve the rust resistance and adhesion to metal materials of the cured aqueous resin composition.
[0233] <Method for manufacturing waterborne resin compositions>
[0234] The aqueous resin composition of this embodiment can be manufactured by mixing an aqueous resin emulsion (α), a curing agent (β), a curing accelerator (γ), and other components as needed. Known methods can be used as a method for mixing the components contained in the aqueous resin composition of this embodiment.
[0235] The aqueous resin composition of this embodiment includes an aqueous resin emulsion (α), a curing agent (β), and a curing accelerator (γ). Therefore, it becomes a composition that can be cured at room temperature for a short time, resulting in a coating film with good initial water resistance and excellent humid heat adhesion to metallic materials.
[0236] Coating
[0237] The coating in this embodiment is composed of a cured product of the aqueous resin composition of this embodiment.
[0238] The coating of this embodiment can be laminated with a coating consisting of a base layer disposed on the lower layer of a coating film composed of a cured product of the aqueous resin composition of the present invention, and / or a top layer disposed on the upper layer, as needed.
[0239] <Coating manufacturing method>
[0240] Next, a method for manufacturing a coating film composed of the cured product of the aqueous resin composition of this embodiment will be described in detail.
[0241] In the coating manufacturing method of this embodiment, firstly, an aqueous resin emulsion (α), a curing agent (β), a curing accelerator (γ), and other components as needed are mixed. This prepares the aqueous resin composition of this embodiment (mixing step). Next, the aqueous resin composition obtained in the mixing step is applied to the surface to be coated (coating step).
[0242] In the mixing process, the aqueous resin emulsion (α), curing agent (β), curing accelerator (γ), and other components as needed are mixed and stirred using a known method. This yields an aqueous resin composition in which each component is dispersed. The stirring in the mixing process can be performed, for example, using a Robomix (manufactured by Premium Co., Ltd.). To ensure sufficient dispersion of the components in the aqueous resin composition of this embodiment, stirring in the mixing process is preferably performed for 5 minutes or more. Furthermore, to inhibit the curing of the resin components in the aqueous resin composition, the stirring time is preferably set to 1 hour or less.
[0243] In the coating process, an aqueous resin composition is applied to the surface of the object to be coated. Materials forming the surface to be coated include, for example, metals such as iron. The surface to be coated may also be pre-treated with a primer or base coat.
[0244] As a method for coating the waterborne resin composition, known methods can be used, such as using a brush, roller, etc., but are not limited thereto. In addition, in order to inhibit the curing of the resin components contained in the waterborne resin composition before the end of the coating process, the coating process is preferably completed within 1 hour after the end of the mixing process, and more preferably within 30 minutes.
[0245] In the coating manufacturing method of this embodiment, it is preferable to perform a curing process after the coating process to cure the coating obtained by coating the surface.
[0246] In the curing process, the resin components contained in the water-based resin composition are cured by drying and aging the coated surface of the workpiece to which the water-based resin composition is applied. The curing time varies depending on the temperature of the curing atmosphere. For example, it is preferable to perform the curing at room temperature (20°C) for 5 hours or more, preferably at 40°C for 1 hour or more, and preferably at 60°C for 5 minutes or more.
[0247] The coating of this embodiment is composed of a cured product of the aqueous resin composition of this embodiment. Therefore, it exhibits good initial water resistance and excellent adhesion to metallic materials under humid heat.
[0248] Furthermore, in the coating film manufacturing method of this embodiment, an aqueous resin composition is prepared by mixing an aqueous resin emulsion (α), a curing agent (β), and a curing accelerator (γ), and then applied to the surface to be coated. Therefore, a coating film of this embodiment, consisting of a cured product of the aqueous resin composition of this embodiment, can be formed.
[0249] <Water-based Resin Composition Kit>
[0250] Next, the aqueous resin composition kit of this embodiment will be described in detail.
[0251] The aqueous resin composition kit of this embodiment is a kit in which the components of the aqueous resin composition of this embodiment are stored separately as a first liquid and a second liquid. The first liquid in the aqueous resin composition kit of this embodiment contains an aqueous resin emulsion (α). The second liquid contains a curing agent (β) and a curing accelerator (γ).
[0252] The coating film of this embodiment can be manufactured using the aqueous resin composition kit of this embodiment. That is, the aqueous resin composition of this embodiment is prepared by mixing the first liquid and the second liquid in the aqueous resin composition kit of this embodiment (mixing step). Then, the aqueous resin composition is applied to the surface to be coated in the same manner as the coating film manufacturing method described above (coating step).
[0253] In this embodiment of the aqueous resin composition kit, a first liquid containing an aqueous resin emulsion (α) and a second liquid containing a curing agent (β) and a curing accelerator (γ) are stored separately. Therefore, in this embodiment, the resin component contained in the aqueous resin emulsion (α) will not react with the curing agent (β) and cure during storage, resulting in excellent storage stability. It should be noted that the first liquid and the second liquid can also be stored separately in different containers, etc. The shape and raw material of the containers can be arbitrarily selected. The container containing the first liquid and the container containing the second liquid can be separated from each other or can be in contact with each other.
[0254] In addition, by using the aqueous resin composition kit of this embodiment, as in the case of using the aqueous resin composition of this embodiment, a coating film with good initial water resistance and good wet and hot adhesion to metal materials can be obtained.
[0255] <Application Areas>
[0256] The aqueous resin composition of the present invention can be used in various fields. The aqueous resin composition of the present invention is particularly suitable for use as a surface anti-corrosion coating for outdoor metal products such as iron towers, bridges, ships, and harbor facilities.
[0257] Articles having a coating film formed from the cured product of the aqueous resin composition of the present invention, i.e., the objects to which the aqueous resin composition of the present invention is applied, can be arbitrarily selected. Specifically, examples of applicable objects include, for instance, metal products used outdoors such as iron towers, bridges, ships, and harbor facilities; various household goods; home appliances such as refrigerators; amusement equipment installed in amusement parks / parks; sporting goods; buildings (interior decoration, exterior decoration, etc.); various industrial products and parts including transportation machinery / machine tools; automobile bodies and chassis; railway vehicle bodies and underfloor equipment; ships; shipping containers; and aircraft.
[0258] Example
[0259] The present invention will now be described in detail using examples. It should be noted that the following examples do not limit the scope of the invention, and all examples implemented without departing from the scope of this description are included within the technical scope of the present invention.
[0260] <1. Synthesis of Aqueous Resin Emulsion (α)>
[0261] (Aqueous resin emulsion (α-1))
[0262] 158 parts by mass of ion-exchanged water were added to a separable flask equipped with a condenser, thermometer, stirrer, and dropping funnel, and the temperature was raised to 60°C. Nitrogen gas was blown into the contents of the separable flask for deoxygenation. An emulsion consisting of methyl methacrylate, 2-ethylhexyl acrylate, methacrylic acid, hydrogenated bisphenol A epoxy resin, sodium dodecylbenzenesulfonate as an emulsifier, and 356 parts by mass of ion-exchanged water, as shown in Table 1, was added dropwise over 3 hours. Simultaneously with the emulsion, a substance formed by dissolving 1.2 parts by mass of potassium persulfate in 41 parts by mass of ion-exchanged water as an oxidant and a substance formed by dissolving 0.4 parts by mass of sodium bisulfite in 21 parts by mass of ion-exchanged water as a reducing agent were added dropwise over 3.3 hours at 60°C to polymerize. After the addition was completed, the mixture was allowed to mature for 1.5 hours. Then, the mixture is cooled, and 0.8 parts by mass of ammonia water, which is an alkaline substance, is added to obtain an aqueous resin emulsion (α-1).
[0263] Table 1 shows the amounts (parts by mass) of each material used in the synthesis of the aqueous resin emulsion (α-1). The values for "ion-exchanged water" in Table 1 indicate the content of ion-exchanged water in the synthesized aqueous resin emulsion (α-1). Additionally, the values in parentheses for the contents of copolymer (X) and polyepoxide (Y) in Table 1 represent the proportion (by mass%) of each material relative to the total amount (100%) of copolymer (X) and polyepoxide (Y).
[0264]
[0265] The following substances are used as the polyepoxide compound (Y) shown in Table 1.
[0266] Hydrogenated bisphenol A type epoxy resin (epoxy equivalent 215 g / mol, manufactured by Kyoei Chemical Co., Ltd., Eporite 4000)
[0267] Bisphenol A type epoxy resin (epoxy equivalent 190 g / mol, manufactured by Mitsubishi Chemical Corporation, JER828)
[0268] 1,6-Hexanediol diglycidyl ether (epoxy equivalent 160 g / mol, manufactured by Kyoei Chemical Co., Ltd., ePolight 1600)
[0269] (Aqueous resin emulsions (α-2)~(α-6))
[0270] In addition to using the materials shown in Table 1 in the amounts (parts by mass) shown in Table 1, aqueous resin emulsions (α-2) to (α-6) are synthesized in the same manner as aqueous resin emulsion (α-1). It should be noted that in aqueous resin emulsions (α-2) to (α-6), the values of "ion-exchanged water" shown in Table 1 also represent the content of ion-exchanged water contained in the synthesized aqueous resin emulsions (α-2) to (α-6) in the same manner as in the synthesized aqueous resin emulsion (α-1).
[0271] <2. Evaluation of Aqueous Resin Emulsions (α)>
[0272] For aqueous resin emulsions (α-1) to (α-6), the following evaluations were performed. The results are shown in Table 2. It should be noted that aqueous resin emulsions (α-6) containing an excess of polyepoxide (Y) were not evaluated due to aggregation during synthesis. In the following description, when aqueous resin emulsions (α-1) to (α-6) are referred to collectively, they are sometimes described as aqueous resin emulsion (α).
[0273] <2-1. Concentration of non-volatile components>
[0274] Weigh 1 g of aqueous resin emulsion (α) into an aluminum pan with a diameter of 5 cm, and dry it at 105 °C for 1 hour in a desiccator under atmospheric pressure with air circulation. Measure the mass of the residue obtained after drying and calculate the ratio (mass%) of the dried residue to the mass of the aqueous resin emulsion (α) before drying.
[0275] <2-2. Residual Epoxy Groups>
[0276] The residual epoxy group content of an aqueous resin emulsion (α) is the ratio of the amount of epoxy groups N1 [mol / g] contained in the synthesized aqueous resin emulsion (α) to the total amount of epoxy groups N2 [mol / g] contained in the components used to synthesize the aqueous resin emulsion (α) (including raw materials, initiators, solvents, other additives, etc.).
[0277] The amount of epoxy groups N1 [mol / g] in the synthesized aqueous resin emulsion (α) was determined by the method described below. Excess hydrogen chloride was added to react with the epoxy groups relative to the total amount of epoxy groups contained in the components (raw materials) used in the synthesis of the aqueous resin emulsion (α). Then, the unreacted hydrogen chloride was titrated with potassium hydroxide to confirm the amount of residual hydrogen chloride. At this time, potassium hydroxide was consumed by reacting with acidic components, represented by carboxylic acids contained in the aqueous resin emulsion (α). Therefore, the result of this determination was corrected beforehand by titrating the amount of acidic components using a blank determination without hydrogen chloride. The specific determination steps are described in (i) to (ii) below.
[0278] (i) Blank determination (confirmation of the amount of acidic components)
[0279] Aqueous resin emulsion (α) was measured in W1 [g] (5g in this example and comparative example) into a 100mL Erlenmeyer flask, and 25g of tetrahydrofuran (THF) was added. The mixture was stirred with a magnetic stirrer to prepare a homogeneous solution. 0.15mL of 0.1% (w / w) cresol red aqueous solution was added to this solution as an indicator. The solution was titrated with 0.1M potassium hydroxide / ethanol solution while stirring. After adding the potassium hydroxide / ethanol solution, the point where the purple color lasted for 30 seconds was taken as the equivalence point. The amount of potassium hydroxide / ethanol solution used in this titration was set as V. KOH1 [mL].
[0280] (ii) This measurement
[0281] The aqueous resin emulsion (α) was measured in W2 [g] (5g in this example and comparative example) into a 100mL Erlenmeyer flask, and 25g of THF was added. The mixture was stirred with a magnetic stirrer until dissolved. A 0.2M hydrogen chloride / dioxane solution was then added, and the mixture was stirred for 1 hour to prepare a homogeneous solution. The amount of hydrogen chloride / dioxane solution added here was set to V. HCl [mL] (25 mL in this example and comparative example). 0.15 mL of a 0.1% (w / w) aqueous solution of cresol red was added to the solution as an indicator. The solution was titrated with a 0.1 M potassium hydroxide / ethanol solution while stirring. After adding the potassium hydroxide / ethanol solution, the point where the purple color lasted for 30 seconds was taken as the equivalent point. The amount of potassium hydroxide / ethanol solution used in this titration was set as V. KOH2 [mL].
[0282] From the values obtained in (i) and (ii), it can be seen that the amount of epoxy group N1 [mol / g] in each 1g of aqueous resin emulsion (α) can be calculated by the following formula (4).
[0283] N1=(0.2×V HCl / 1000-0.1×V KOH2 / 1000) / W2+(0.1×V KOH1 / 1000) / W1…(4)
[0284] The total amount of epoxy groups N2 [mol / g] in the components (raw materials) used in the synthesis of aqueous resin emulsion (α) is determined by the mass m of each component. i [Parts by mass] (i = 1, 2, 3, ...), Epoxy equivalent EP i [g / mol], calculated using the following equation (5). Here, the components used in the synthesis of the aqueous resin emulsion (α) refer to all the components listed in Table 1 as raw materials for the aqueous resin emulsion (α).
[0285] N2=Σ(m i / EP i ) / Σm i …(5)
[0286] It should be noted that for compounds that do not contain epoxy groups, such as methyl methacrylate and deionized water, 1 / EP i =0.
[0287] Based on the amount of epoxy groups calculated in this way, the residual epoxy group content of the aqueous resin emulsion (α) is expressed as 100×N1 / N2 [mol%).
[0288] <2-3. Content of epoxy groups in non-volatile components, and content of epoxy groups in components (X)+(Y)>
[0289] The concentration C of the non-volatile component obtained by the above method S [mass %], epoxy group content N1 in the aqueous resin emulsion (α), and total epoxy group content N2 in the raw materials, based on the above-described formula (2), calculate the epoxy group content R in the non-volatile components of the aqueous resin emulsion (α). EP [mol / g].
[0290] R EP =N1 / (C S / 100)…(2)
[0291] Furthermore, using the epoxy group content N1 in the aqueous resin emulsion (α) obtained by the above method, the total mass α[g] of all components (raw materials) used in the synthesis of the aqueous resin emulsion (α), the mass X[g] of the raw materials used in the copolymer (X), and the mass Y[g] of the raw materials used in the polyepoxide compound (Y), the epoxy group content R in component (X)+(Y) is calculated based on the following formula. EP [mol / g].
[0292] R in (X)+(Y) EP =N1 / {(X+Y) / α}
[0293] <2-4. Carboxyl group content in non-volatile components, carboxyl group content in component (X)+(Y)>
[0294] The total amount of carboxyl groups N3 [mol / g] contained in the components (raw materials) used in the synthesis of aqueous resin emulsion (α) is determined by the mass m of each component. i [parts by mass] (i = 1, 2, 3, ...), and carboxyl equivalent CX i [g / mol], calculated using the following formula (6). Here, the components used in the synthesis of the aqueous resin emulsion (α) refer to all the components listed in Table 1 as raw materials for the aqueous resin emulsion (α).
[0295] N3=Σ(m i / CX i ) / Σm i …(6)
[0296] Based on N3 obtained from this, and using equation (3) described above, the content R of carboxyl groups in the non-volatile components of the aqueous resin emulsion (α) can be calculated. CX [mol / g].
[0297] R CX ={N3-(N2-N1)} / (C S / 100)…(3)
[0298] Furthermore, using the epoxy group content N1 in the aqueous resin emulsion (α), the total epoxy group content N2 in the raw materials, the total carboxyl group content N3 in the components (raw materials) used in the synthesis of the aqueous resin emulsion (α), the total mass α[g] of all components (raw materials) used in the synthesis of the aqueous resin emulsion (α), the mass X[g] of the raw materials used in the copolymer (X), and the mass Y[g] of the raw materials used in the polyepoxide compound (Y) obtained by the above method, the carboxyl group content R in component (X)+(Y) is calculated based on the following formula. CX [mol / g].
[0299] R in (X)+(Y) CX ={N3-(N2-N1)} / {(X+Y) / α}
[0300] <2-5.pH>
[0301] The pH was measured at 23°C using a pH meter (manufactured by Toa Discrete Co., Ltd., glass electrode hydrogen ion concentration indicator HM-30G).
[0302] <2-6. Viscosity>
[0303] The viscosity of an aqueous resin emulsion (α) was determined using the following conditions and apparatus.
[0304] Temperature: 23℃
[0305] Measuring equipment: Type B viscometer
[0306] Rotor: No.1
[0307] Speed: 60 rpm
[0308] <2-7. Glass Transition Temperature>
[0309] The glass transition temperature Tg of copolymer (X) is calculated using the above formula (1).
[0310] <2-8. Dispersion>
[0311] Visually observe the state of the freshly synthesized aqueous resin emulsion (α) and evaluate it according to the following criteria.
[0312] ○ (Pass): No aggregation, precipitation, separation, or gelation was observed.
[0313] × (Unacceptable): At least one of the following was observed: aggregation, precipitation, separation, and gelation.
[0314] <2-9. High Temperature Stability>
[0315] The high-temperature stability of the aqueous resin emulsion (α) was evaluated as follows. First, the aqueous resin emulsion (α) was added to a 70 ml glass bottle and sealed tightly, then allowed to stand at 60°C for 7 days. Then, the state of the aqueous resin emulsion (α) in the glass bottle was visually observed, and evaluated according to the following criteria.
[0316] ○ (Pass): No aggregation, thickening, precipitation, separation, or gelation was observed.
[0317] × (Unacceptable): At least one of the following was observed: agglomeration, thickening, precipitation, separation, and gelation.
[0318] Table 2
[0319]
[0320] <2-10. Evaluation Results>
[0321] As shown in Table 2, the aqueous resin emulsions (α-1) to (α-5) exhibit good dispersibility and high-temperature stability. In contrast, the aqueous resin emulsion (α-6) with an excessive content of polyepoxide (Y) shows insufficient dispersibility.
[0322] Therefore, relative to the total amount of raw materials (monomers) and polyepoxides (Y) used in copolymer (X), the aqueous resin emulsion (α) with an addition amount of 20-98% by mass of (meth)acrylate (A), an addition amount of 0.1-10% by mass of olefinic unsaturated carboxylic acid (B), and an addition amount of 1-40% by mass of polyepoxides (Y) exhibits excellent dispersibility and high-temperature stability.
[0323] <3. Examples 1-10 and Comparative Examples 1-15 (Preparation of Aqueous Resin Compositions)>
[0324] To 100 parts by weight of the aqueous resin emulsion (α) shown in Tables 3 to 5 (40% by weight of non-volatile components), 60 parts by weight of ion-exchanged water, curing agent (β) and curing accelerator (γ) shown in Tables 3 to 5 were added in the amounts (parts by weight) shown in Tables 3 to 5. The mixture was stirred for 10 minutes to prepare the aqueous resin compositions of Examples 1 to 10 and Comparative Examples 1 to 15.
[0325] In Tables 3 to 5, the “active hydrogen equivalent relative to epoxy group” for each curing agent (β) represents the equivalent of active hydrogen contained in the aromatic polyamine (F) with active hydrogen contained in the curing agent (β) relative to the equivalent of epoxy group contained in the aqueous resin emulsion (α).
[0326] The "mol number relative to epoxy groups" in the curing accelerator (γ) refers to the number of mol equivalents of epoxy groups contained in the curing accelerator (γ) relative to the amount of epoxy groups contained in the aqueous resin emulsion (α).
[0327] In Table 3, “MXDA content [mass %]” represents the MXDA content in the aromatic polyamine (F) containing active hydrogen contained in the curing agent (β).
[0328] As the aromatic polyamines (F) shown in Tables 3 to 5, Gaskamine 328 (Mitsubishi Gas Chemical Co., Ltd.) or m-phenylenediamine (MXDA) (Mitsubishi Gas Chemical Co., Ltd.) were used.
[0329] The active hydrogen equivalent in MXDA is 34 g / mol.
[0330] Gaskamine 328 contains an active hydrogen equivalent of 55 g / mol. Gaskamine 328 is a mixture of a modifier of MXDA and MXDA. Gaskamine 328 contains 73.3% by mass of a compound represented by general formula (1-1) as a modifier of MXDA. Gaskamine 328 contains 26.7% by mass of MXDA.
[0331] As the aliphatic polyamines shown in Tables 3 to 5, EH-8051 (trade name: Adekharner EH-8051, manufactured by ADEKA Co., Ltd.) or ED-600 (trade name: Jefamine ED-600, manufactured by Hantsman Japan Co., Ltd.) are used.
[0332] The active hydrogen equivalent contained in Adicaharna EH-8051 is 180 g / mol.
[0333] The active hydrogen equivalent in JEFFAMINE ED-600 is 132 g / mol.
[0334]
[0335]
[0336]
[0337] <4. Evaluation of coating and film>
[0338] The aqueous resin compositions of Examples 1-10 and Comparative Examples 1-15 were used respectively to form coatings and films by the methods shown below, and the following items were evaluated. The results are shown in Tables 3-5. The coatings and films of Examples 1-10 and Comparative Examples 1-15 were formed by applying the aqueous resin compositions to the surface to be coated within 1 hour after the preparation of the aqueous resin compositions (coating was completed within 1 hour after the mixing process).
[0339] <4-1. Method for determining the yield strength of the membrane>
[0340] The aqueous resin composition was applied by casting onto the entire surface of a horizontally placed rectangular sheet made of polyethylene film, measuring 90 mm in length and 190 mm in width. After drying at 23°C for 72 hours, it was cured at 50°C for 24 hours to produce a coating film with a thickness of approximately 300 μm. The resulting coating film was then peeled off from the sheet. The resulting film was cut into rectangles 10 mm wide and 30 mm long to serve as test pieces.
[0341] The following tests were conducted with the longitudinal direction of the test piece as the tensile direction. The thickness of the test piece was measured using a QuikMickro (registered trademark) MDQ-MX manufactured by Mitsutoyo Co., Ltd. Measurements were taken at three locations for each test piece, and the average of the three measurements was taken as the thickness t [mm] of the test piece. The thickness of the test piece was approximately 300 μm.
[0342] The yield strength of the membrane was tested using an AutoGrav AG-X (manufactured by Shimadzu Corporation) and the method shown below. The chuck spacing was set to 10 mm, and the chucks were clamped on both sides of the test specimen along its length. The test specimen was stretched at a speed of 100 mm / min under an atmosphere of 23°C and 50% relative humidity (RH).
[0343] If the distance between the chucks is set to L [mm], and the change in the length of the test piece (the difference between the distance between the chucks during the test and the distance between the chucks before the test) is set to ΔL [mm], then the strain S is calculated from 100 × ΔL / L [%). Furthermore, the load applied to the test piece (the measured load) is set to F [N], and the maximum value of the load until the test piece breaks is set to F. max [N], the point that initially satisfies the following condition from the start of the experiment will be set as the yield point Y(S). y F y ).
[0344] (Condition for yield point)
[0345] Strain S is 2% or more (S y ≥2%.
[0346] As the strain S increases, the load F changes from increasing to decreasing.
[0347] dF / dS < 0 continues until F = F y -0.01F max .
[0348] In S≤S y At +0.05%, F > F does not exist. y point.
[0349] The membrane yield strength is the stress σ applied to the test piece at the yield point Y. y It can be calculated using the formula shown below.
[0350] σ y [N / mm 2 ] = F y / (W×t)
[0351] In the formula, W is the width of the test piece [mm], and t is the thickness of the test piece [mm].
[0352] <4-2. Initial water resistance>
[0353] On the surface of cold-rolled steel sheet (800μm thickness), a brush was used to apply a solution at a weight of 50g / m² per unit area. 2The aqueous resin composition was coated and dried at 23°C for 1 day (24 hours). This resulted in a rectangular test piece with a coating on its surface, measuring 70 mm in length and 150 mm in width. The coating thickness of the test piece was approximately 100 μm.
[0354] The prepared test piece was immersed in ion-exchange water and sealed, and stored at 23°C for 7 days. Then, the test piece was removed from the ion-exchange water.
[0355] For the removed test pieces, the area of rust formation ("area %) and the area of expansion formation ("area %) in the test area were determined using the method shown below. The test area was defined as a rectangular region of 45 mm long and 125 mm wide within the coating of the test piece.
[0356] Visually observe the appearance of the test piece, and designate areas on the coating surface that have discolored to brown or black due to storage as rusted areas. For each rusted area within the test area, measure its dimensions using a ruler and calculate the total area of the rusted areas within the test area. Use the results to determine the percentage of rusted area relative to the total area of the test area.
[0357] The appearance of the test pieces was visually observed and evaluated by touch, investigating any areas of swelling on the coating surface due to storage. The results showed that the planar shapes of the swollen areas were all approximately circular. Therefore, for each swollen area, the planar shape was considered a perfect circle, and the maximum straight-line distance between the outlines of the swollen areas was measured with a ruler; this result was taken as the diameter. Then, using the diameters of each swollen area, the total area of the swollen areas within the test area was calculated, and the percentage of swollen area relative to the total area of the test area was determined.
[0358] <4-3. The adhesion of the coating to metallic materials under humid and hot conditions>
[0359] On the surface of cold-rolled steel sheet (800μm thickness), a brush was used to apply a solution at a weight of 50g / m² per unit area. 2 The aqueous resin composition was coated and dried at 23°C for 7 days, thus forming a rectangular test piece with a coating on its surface, measuring 70 mm in length and 150 mm in width. The test area was defined as a rectangular region within the coating of the test piece, measuring 45 mm in length and 125 mm in width. The coating thickness of the test piece was approximately 100 μm.
[0360] The test pieces prepared in this way were stored in a constant temperature bath at 40°C and 98% relative humidity (RH) for 3 days. Then, following JIS K-5400 (1990) "8.5.2 Checkerboard Tape Method", checkerboard cuts (100 squares) with 1mm intervals were made with a cutter, penetrating the coating formed in the test area of the test piece, and a celestial tape (registered trademark) was applied. After 1 hour of application, the celestial tape (registered trademark) was peeled off, and the number of squares remaining that did not peel off from the steel plate was counted. Then, based on the number of squares remaining that did not peel off, the hygrothermal adhesion of the coating to the metal material was evaluated.
[0361] <4-4. Evaluation Results>
[0362] As shown in Table 3, the yield strength of the films formed by the cured resin compositions of Examples 1 to 10, which contain aqueous resin emulsions (α-1) to (α-5) and a curing agent (β) as an aromatic polyamine, is 10 N / mm². 2 The above indicates that the membrane has high yield strength.
[0363] In addition, in the evaluation of the initial water resistance of the coatings formed by the cured resin compositions of Examples 1 to 10, which were cured by curing at room temperature for a short time (1 day (24 hours) at 23°C), the area of swelling was less than 30% and the area of rust formation was less than 15%, indicating good initial water resistance.
[0364] Furthermore, the coatings formed by the cured resin compositions of Examples 1 to 10, which are cured by room temperature curing, all showed a 100 / 100 result in terms of hygrothermal adhesion to metal materials, indicating good hygrothermal adhesion to metal materials.
[0365] Furthermore, as shown in Tables 4 and 5, the film yield strength of the cured films composed of the aqueous resin compositions of Comparative Examples 1 to 15 is 10 N / mm². 2 The above indicates that the membrane has high yield strength.
[0366] However, the coatings formed by the cured aqueous resin compositions of Comparative Examples 1-6, 8-10, 12-14 which use aliphatic polyamines as curing agents (β), Comparative Examples 7 and 11 which contain 1.5 equivalents or more of aromatic polyamines as curing agents (β), and Comparative Example 15 which contains 1.5 mol or more of curing accelerators (γ) relative to 1 equivalent of epoxy groups, all showed poorer results in terms of hygrothermal adhesion to metal materials compared to the coatings formed by the cured aqueous resin compositions of Examples 1-10.
[0367] Industrial availability
[0368] According to the present invention, a water-based resin composition and a water-based resin composition kit can be provided, which can be cured by short-time curing at room temperature to form a coating film with excellent initial water resistance and good adhesion to metal materials under humid heat.
Claims
1. An aqueous resin composition comprising an aqueous resin emulsion (α), a curing agent (β), and a curing accelerator (γ); The aqueous resin emulsion (α) comprises a copolymer (X), a polyepoxide compound (Y) having two or more epoxy groups per molecule and no olefinic unsaturated bonds, and an aqueous medium (Z). The content of the polyepoxide (Y) is 1 to 40% by mass relative to the total amount of the copolymer (X) and the polyepoxide (Y). The copolymer (X) comprises structural units derived from (meth)acrylate (A) and structural units derived from olefinic unsaturated carboxylic acids (B). The content of the structural unit derived from (meth)acrylate (A) is 20-98% by mass relative to the total amount of the copolymer (X) and the polyepoxide (Y). Relative to the total amount of the copolymer (X) and the polyepoxide compound (Y), the content of the structural unit derived from the olefinic unsaturated carboxylic acid (B) is 0.1 to 10% by mass, and the structural unit derived from (meth)acrylate (A) includes a structural unit derived from hydrophilic (meth)acrylate (A1), wherein the alcohol-derived portion of the hydrophilic (meth)acrylate (A1) has 2 or fewer carbon atoms. The content of the structural unit derived from the hydrophilic (meth)acrylate (Al) is 15-98% by mass relative to the total amount of the copolymer (X) and the polyepoxide (Y). One or both of the copolymer (X) and the polyepoxide compound (Y) contain carboxyl groups. The curing agent (β) comprises an aromatic polyamine (F) having active hydrogen atoms that are reactive to epoxy groups. Regarding the content of the aromatic polyamine (F) contained in the curing agent (β), relative to the amount of epoxy groups contained in the aqueous resin emulsion (α), the amount of active hydrogen contained in the aromatic polyamine (F) is 0.10 equivalents or more and 1.50 equivalents or less. The curing accelerator (γ) comprises a tertiary amine, which does not have active hydrogen atoms reactive to epoxy groups. The content of the curing accelerator (γ) is 0.0070 mol or more and 1.5 mol or less relative to the epoxy group equivalent contained in the aqueous resin emulsion (α).
2. The aqueous resin composition according to claim 1, wherein the (meth)acrylate (A) is composed of an alkyl (meth)acrylate.
3. The aqueous resin composition according to claim 1 or 2, wherein the olefinic unsaturated carboxylic acid (B) comprises at least one of α,β-unsaturated monocarboxylic acid, α,β-unsaturated dicarboxylic acid, and a vinyl compound containing a carboxyl group.
4. The aqueous resin composition according to claim 1 or 2, wherein the polyepoxide (Y) is selected from at least one of bisphenol type epoxy compounds, hydrogenated bisphenol type epoxy compounds, diglycidyl ether, triglycidyl ether, tetraglycidyl ether, diglycidyl ester, triglycidyl ester and tetraglycidyl ester.
5. The aqueous resin composition according to claim 1 or 2, wherein the copolymer (X) is composed of structural units derived from (meth)acrylate (A) and structural units derived from olefinic unsaturated carboxylic acids (B).
6. The aqueous resin composition according to claim 1 or 2, wherein the copolymer (X) comprises structural units derived from an olefinically unsaturated aromatic compound (C) having a benzene ring and olefinically unsaturated bonds.
7. The aqueous resin composition according to claim 6, wherein the olefinic unsaturated aromatic compound (C) is an aromatic vinyl compound.
8. The aqueous resin composition according to claim 1 or 2, wherein the aromatic polyamine (F) comprises an aromatic polyamine having two or more benzene rings per molecule.
9. The aqueous resin composition according to claim 1 or 2, wherein the aromatic polyamine (F) comprises a compound represented by the following general formula (1-1), In equation (1-1), A 2 A 3 Each of these can be independently represented as 1,2-phenylene, 1,3-phenylene, or 1,4-phenylene, where n represents an integer from 1 to 12.
10. The aqueous resin composition according to claim 9, wherein the aromatic polyamine (F) comprises a compound represented by the above general formula (1-1) and m-phenylenediamine.
11. The aqueous resin composition according to claim 1 or 2, wherein the curing accelerator (γ) is at least one compound selected from aliphatic tertiary amines, alicyclic tertiary amines, and heteroaromatic tertiary amines.
12. The aqueous resin composition according to claim 1 or 2, wherein the aqueous resin emulsion (α) is an emulsion formed by emulsion polymerization of monomers forming the structural units of the copolymer (X) in the aqueous medium (Z) in the presence of the polyepoxide compound (Y).
13. The aqueous resin composition according to claim 1 or 2, wherein the carboxyl group content in the total amount of the copolymer (X) and the polyepoxide compound (Y) is 0.10 × 10⁻⁶. -4 Above mol / g.
14. The aqueous resin composition according to claim 1 or 2, wherein the epoxy group content in the total amount of the copolymer (X) and the polyepoxide compound (Y) is 0.50 × 10⁻⁶. -4 Above mol / g.
15. A coating film comprising a cured product of the aqueous resin composition of claim 1.
16. A method for manufacturing a coating film, comprising a mixing step of preparing the aqueous resin composition of claim 1 by mixing an aqueous resin emulsion (α), a curing agent (β), and a curing accelerator (γ); and a coating step of applying the aqueous resin composition to a surface to be coated.
17. The method for manufacturing a coating film according to claim 16, wherein the coating process is completed within 1 hour after the mixing process is completed.
18. A waterborne resin composition kit, wherein the components of the waterborne resin composition of claim 1 are separated into a first liquid and a second liquid for storage. The first liquid comprises the aqueous resin emulsion (α). The second liquid contains the curing agent (β) and the curing accelerator (γ).
Citation Information
Patent Citations
Coating composition for thickly coating use
JP2011089092A
Epoxy resin imbibed polymer particles
JP2014065914A
Display system
JP2021092839A
Acrylic / epoxy hybrid materials for laminating adhesive applications
WO2017112018A1
Aqueous resin emulsion, method for producing same, and aqueous resin composition
CN112703207A